Branchial Anomalies: Diagnosis and Management. (4th March 2014) - Prasad, Sampath Chandra; Azeez, Arun; Thada, Nikhil Dinaker; Rao, Pallavi; Bacciu, Andrea; Prasad, Kishore Chandra
Abstract : Objective . To find out the incidence of involvement of individual arches, anatomical types of lesions, the age and sex incidence, the site and side of predilection, the common clinical features, the common investigations, treatment, and complications of the different anomalies. Setting . Academic Department of Otolaryngology, Head and Neck Surgery. Design . A 10 year retrospective study. Participants . 30 patients with clinically proven branchial anomalies including patients with bilateral disease totaling 34 lesions. Main Outcome Measures . The demographical data, clinical features, type of branchial anomalies, and the management details were recorded and analyzed. Results and Observations . The mean age of presentation was 18.67 years. Male to female sex ratio was 1.27 : 1 with a male preponderance. Of the 34 lesions, maximum incidence was of second arch anomalies (50%) followed by first arch. We had two cases each of third and fourth arch anomalies. Only 1 (3.3%) patients of the 30 presented with lesion at birth. The most common pathological type of lesions was fistula (58.82%) followed by cyst. 41.18% of the lesions occurred on the right side. All the patients underwent surgical excision. None of our patients had involvement of facial nerve in first branchial anomaly. All patients had tracts going superficial to the facial nerve. Conclusion . Confirming the extent of the tract is mandatory before any surgery as these lesions pass in relation to some of the most vital structures of the neck. Surgery should always be the treatment option. injection of dye, microscopic removal and inclusion of surrounding tissue while excising the tract leads to a decreased incidence of recurrence.